ANALYSIS OF INFLATION EFFECT AND INTEREST RATE LEVEL OF INVESTMENT IN INDONESIA - Wisnu Satria; Eriesnawaty Nurjannah (Riset Ekonomi Pembangunan, 2020)
The purpose of this study was to find out and analyze the effect of inflation on investment and interest rates on investment in Indonesia from 2006 to 2015. This type of research is quantitative descriptive and data source retrieval with literature study techniques. The analytical method used in this study is regression time lag analysis. Based on the data analyzed in this study there are several conclusions as follows: 1) inflation has a significant effect on investment 2) interest rates have a significant effect on investment.